Structural Labour Market Crisis in Bulgaria: Demographic Decline, Labour Shortages and Macroeconomic Implications (2013 – 2025) - Angelov, Asen (Research Papers, 2025)
This article examines Bulgaria’s structural labour market crisis during the period 2013 – 2025, characterized by demographic decline, persistent labour shortages and weakening macroeconomic performance. Despite historically low unemployment rates of 3.6 – 4.2 percent in 2024 – 2025, the labour market operates under severe structural constraints driven by population ageing, shrinking labour force and regional depopulation. Using established theoretical models such as Okun’s law, NAIRU and the Phillips curve, combined with empirical data from UN DESA, Eurostat, NSI, BNB and the World Bank, the study demonstrates that Bulgaria’s low unemployment reflects labour market overheating rather than sustainable economic strength. Wage growth has consistently exceeded productivity, foreign direct investment has weakened, and the demographic contraction has sharply reduced the economy’s potential growth. The findings highlight deepening structural imbalances that restrict competitiveness and long-term development. The study concludes that comprehensive reforms in demographic, educational and regional policy are essential for restoring Bulgaria’s economic potential.